GUIDANCE OF INNOVATION IN CALISTUNG LEARNING WITH YOUTUBE AND STUDENT LEARNING MOTIVATION SDN 110410 BATU MARIRING - Wika Widuri; Pristiyono; Meisa Fitri Nasution (RADJA PUBLIKA, 2025)
Quality Education is part of the Sustainable Development program initiated by the government that in 2045 Indonesia will have a competitive golden generation that is ready to face future situations. Education is the right way to produce human resources and intellectual generations. Including the Thematic Community Service (KKN) Mentoring program implemented for 4 months August-November 2024. This mentoring method is implemented in a structured manner with a mature program starting from situation analysis, solutions, mechanisms and feedback.The results of this program show that teachers and students have good learning motivation if there is good use of media such as Youtube starting from reading, writing and arithmetic. Psychologically, this program affects the psychology of teachers to remain role models and enthusiastic about educating the nation's children and to students to be wise in using the Youtube application, especially related to learning content, reading, writing and how to count.